Journalism, media and technology trends and predictions 2018 - Newman, N (Reuters Institute for the Study of Journalism, 2018)
This report looks ahead at the trends in media and technology that will shape the news industry in 2018. This will be a critical year for the relationship between publishers and platforms, as companies like Google and Facebook fight a rising tide of criticism about their impact on society – and on the journalism. News business models are shifting from advertising towards subscription and other forms of reader payment. 2018 will also see a renewed focus on data as the ability to collect, process, and use it effectively proves a key differentiator. Media companies will be actively moving customers from the ‘anonymous to the known’ so they can develop more loyal relationships and prepare for an era of more personalised services. The era of Artificial Intelligence will bring new opportunities for creativity and for efficiency but also for greater misinformation and manipulation.